Quality of Public Services: The Role of State Civil Apparatus in Realizing Good Governance - Madjid, Udaya (Journal of Ecohumanism, 2024)
Good governance is considered crucial in providing effective, transparent and accountable public services, so it is the main key to sustainable development. This research aims to analyze the role of the State Civil Apparatus (ASN) in improving the quality of public services as an integral part of efforts to achieve good governance. This research uses a qualitative approach with descriptive methods. The results of this research highlight the central role of the State Civil Apparatus (ASN) in realizing Good Governance, especially in improving the quality of public services. The findings show that service efficiency can be improved through efficient management of resources and administrative processes by ASN. Transparency, accountability and active participation of ASN in the decision-making process have also been proven to have a positive impact on the quality of public services. Involving the public in decision making not only increases policy responsiveness, but also creates strong legitimacy. In conclusion, ASN who play an active role in implementing the principles of Good Governance are able to form a government environment that is effective, trustworthy, and able to better meet the needs of the community.